Determining soil and landscape requirements of cotton for use in land suitability assessment in Iran - GHORBAN ALI ROSHANI; S. A. R. SEYED JALALI (Cotton Research Journal, 2023)
The strategic importance of cotton as a source of fiber and edible oil for people, feed for animal, and a commodity for job creationmakes cotton cultivation an economically important activity. Of late, some challenges have led to a decline in cotton cultivation inIran in recent decades. This declining trend has prompted the Ministry of Agriculture, Jihad to put on its agenda a plan for attaining self-sufficiency in cotton production by 2025. To realize this, it is necessary to identify and prioritize areas in the country with suitable  production potential for cotton cultivation. This can be done by conducting systematic land suitability assessment studies and analyzing the characteristics and quality of soil and climatic resources for cotton cultivation. Hence, the objective of this study was to determine the soil and landscape requirements for cotton production that will be used to evaluate land suitability for cotton.